Efficacy and safety of diosmectite in acute childhood diarrhoea: a meta-analysis. Issue 7 (17th March 2015) - Das, Rashmi Ranjan; Sankar, Jhuma; Naik, Sushree Samiksha
Abstract : Objective: We evaluated the role of diosmectite as an add-on treatment to the 'recommended treatment' of acute diarrhoea in children. Methods: We searched all published literature through the major databases: Medline via Ovid, PubMed, CENTRAL, Embase and Google Scholar till May 2014. Randomised clinical trials comparing diosmectite versus placebo were included (PROSPERO registration: CRD42014013783). Main outcome measures: The primary outcome measures were duration of acute diarrhoea (h), and day-to-day cure rates (%). The secondary outcome measures were stool output (volume), stool output (frequency) and adverse events. Results: Of 384 citations retrieved, a total of 13 randomised clinical trials (2164 children, 1–60 months old) were included in the meta-analysis. A dose of 3–6 grams per day of diosmectite was given for a duration from 3 days until recovery. Compared with placebo, diosmectite significantly decreased the duration of acute diarrhoea (mean difference, −23.39; 95% CI −28.77 to −18.01), and increased the cure rate (%) at day 5 (OR, 4.44; 95% CI 1.66 to 11.84), without any increases in the risk of adverse events. Diosmectite was effective in all types of acute childhood diarrhoea except dysentery. Because, most of the trials were open-label, and there was a high possibility of publication bias, the GRADE evidence generated was of 'low quality'. Conclusions: Diosmectite may be a useful additive in the treatment of acute childhood diarrhoea. As the evidence generated was of 'low quality', future research is needed with higher quality designs before any firm recommendations can be made. Trial registration number: PROSPERO registration: CRD42014013783.